2019
DOI: 10.5751/es-10693-240107
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and institutional degradation in the globalized economy: lessons from small-scale fisheries in the Gulf of California

Abstract: External drivers increasingly impact small-scale fisheries worldwide. As globalization accelerates the flow of information, commodities, and capital across geographic space, neoliberal reforms have fueled the development of the international seafood trade. Small-scale fisheries traditionally driven by local forces and market demands are increasingly nested within the broader structures of global markets and international institutions. Building on existing work that integrates social-ecological systems thinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 119 publications
(223 reference statements)
0
28
1
1
Order By: Relevance
“…Alienation of the informal sector (libres and permisionarios libres) via a lack of access to secure fishing rights, formal sanctions, and exclusion from decision-making processes has also led to tension between formal and informal groups. Previous work in Baja California Sur has found that the permitting structure limits fishers' ability to migrate seasonally in response to seasonal shifts in target species (Sievanen 2014), and that market accessibility privileges wealthy actors (Frawley et al 2019b). In Loreto, participatory processes meant to encourage the inclusion of diverse actors in marine resource management have resulted in internal exclusion, whereby the participation of certain actors and groups is limited (Peterson 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alienation of the informal sector (libres and permisionarios libres) via a lack of access to secure fishing rights, formal sanctions, and exclusion from decision-making processes has also led to tension between formal and informal groups. Previous work in Baja California Sur has found that the permitting structure limits fishers' ability to migrate seasonally in response to seasonal shifts in target species (Sievanen 2014), and that market accessibility privileges wealthy actors (Frawley et al 2019b). In Loreto, participatory processes meant to encourage the inclusion of diverse actors in marine resource management have resulted in internal exclusion, whereby the participation of certain actors and groups is limited (Peterson 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how individuals make decisions and adapt is key to predicting how they will fare under changing conditions in the future (Coulthard and Britton 2015). Heterogeneity among fishers has consequences both for the sustainability of fished populations and for fishers' individual capacity to adapt to future change (Coulthard and Britton 2015, Frawley et al 2019b). Adaptive capacity is defined as the ability of systems to design or change their structure in response to environmental or socioeconomic variability such that they maintain the ability to cope under new circumstances (Adger et al 2005, Armitage andPlummer 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fisheries productivity is expected to decrease across such latitudes (Sumaila et al, 2011) as critical infrastructure and marine habitat are threatened by predicted ocean warming, sea level rise, and increases in the frequency and severity of extreme weather events (Pratchett et al, 2011;Woodruff et al, 2013). In addition, these SSF systems are increasingly embedded in global trade networks and international institutions (Crona et al, 2016), and their high resource dependence, restricted market access, and limited governance capacity make them acutely susceptible to political and economic instability (Lauer et al, 2013;Frawley et al, 2019). Across the Gulf of California, global change is transforming SSFs and the social-ecological systems in which they are embedded (Frawley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these SSF systems are increasingly embedded in global trade networks and international institutions (Crona et al, 2016), and their high resource dependence, restricted market access, and limited governance capacity make them acutely susceptible to political and economic instability (Lauer et al, 2013;Frawley et al, 2019). Across the Gulf of California, global change is transforming SSFs and the social-ecological systems in which they are embedded (Frawley et al, 2019). Though the sector has long been a major source of regional economic development (Sala et al, 2004), the ecology and biodiversity of the region have suffered considerable degradation (Carvajal et al, 2004;Saenz-Arroyo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%